The new challenges for higher education institutions in consequence of new public audit - Monteiro, Lurdes (2016)
This research was carried out in order to investigate the new challenges for public audit in consequence of the recent public accounting changes, specifically the adoption in Portugal the International Public Sector Accounting Standards (IPSAS), because the New Public Management (NPM) implies a new model of public management, pursuing a public sector with more transparency and accountability (Hood, 1991; Dunleavy & Hood, 1994; Barzelay, 2001; Wiesel & Modell, 2014). Thus, the purpose of this research is to demonstrate the need to design strategies, principles and challenges to the courses offered by Higher Education Institutions (HEI), particularly the Bachelor of Accounting and the Master of Accounting of the School of Technology and Management of the Guarda Polytechnic Institute (in Portuguese, ESTG-IPG), to answer to job market of the public entities, in general, and students and teacher’s needs, in particular. On the one hand, as result of the entry into force on January 1, 2010 of Decree Law nº 158/2009 of 13 July (MFAP, 2009), which approved the new Portuguese Accounting Standards System for the private sector and revoked the Official Accounting Plan, approved by Decree Law nº 410/89 of November 21 (MF, 1989), Portugal adheres to the European model of the International Financial Reporting Standards (IFRS) issued by the International Accounting Standards Board (IASB). On the other hand, the Official Plan of Public Accounting for the public sector, approved by Decree Law nº 232/97 of September 3 (MF, 1997), will adheres to the IPSAS issued by the International Public Sector Accounting Standards Board (IPSASB) in a near future. Methodologically, this research relied on a two-track approach. The first takes the form of an editorial review and argument, based on the Portuguese and European legal regime of accounting and auditing and the literature review. The second takes the form of a case study method involving a profound knowledge of the Bachelor of Accounting, approved by Order nº 13997/2012 of October 26 (IPG,2012), that revised the Order nº 21638/2006 of October 24 (IPG, 2006), and the Master of Accounting, approved by Order nº 14928/2011 of November 3 (IPG, 2011), that revised the Order nº 4351/2008 of February 19 (IPG,2008), of the ESTG-IPG.